TANTANGAN PENGEMBANGAN BAITUL MAL WAT-TAMWIL DI PEKANBARU RIAU - KHORNELIS DEHOTMAN; YUSRIALIS YUSRIALIS (Universitas Islam Negeri Imam Bonjol Padang, 2016)
The research theme is the business concept According to Islamic economics. This study aims to identify and analyze what is the challenge of development of BMT as Islamic Micro Finance Institutions (LKMS) are legal entities Credit Unions and Islamic Financing (KSPPS) in the city of Pekanbaru in Riau province. Qualitative data used is sourced from secondary data. Technical studies conducted by the method of literature and observations directly. The results showed that the BMT in Pekanbaru faced with a significant challenge because it is associated with similar challenges faced BMT activists across Indonesia. The challenges faced include external challenges Indonesia's economy, dynamics of banking sector, legal and regulatory problems, Role and Position of Cooperatives. Besides, it is a challenge from within the form. Sharia compliance, Institutional Strengthening and employees. Meanwhile all these challenges can be an opportunity BMT in the future if it can be addressed and managed well and Syar'i.